Interacting Action of Alkali-Silica Reaction and Chloride-Induced Steel Corrosion on The Reinforced Concrete Structures – A Critical Review - Dunu, Williams (CSID Journal of Infrastructure Development, 2023)
The degradation of reinforced concrete (RC) structures amidst the progression of corrosion within alkali-silica reaction (ASR)-affected structures is a complex phenomenon marked by diverse causal factors and repercussions. While the initiation phase of chloride-induced steel corrosion and ASR in RC structures has received extensive scrutiny, insufficient attention has been dedicated to comprehending the propagation phase (tp). Therefore, this study addresses this gap by centering its focus on the propagation phase, driven by the imperative need to formulate efficient and sustainable maintenance, repair, and management strategies for RC structures grappling with the concurrent impacts of degradation mechanisms such as ASR and corrosion. The use of corrosion initiation for predicting the operational lifespan of RC structures has been subject to rigorous examination by researchers and engineers, especially in light of recent breakthroughs in the concrete construction industry. In this context, the present investigation presents early findings, employing durability index tests to analyze the durability attributes of concrete incorporating both reactive and non-reactive materials (aggregates). Furthermore, the study proposes enhancements to prior research endeavors in this domain. While additional data is requisite to ascertain the cumulative influence of ASR and corrosion, conducting a comparative analysis of fluid transport rates through ASR-susceptible and ASR-non-susceptible concretes offers valuable insights into the maintenance and restoration of RC structures afflicted by both corrosion and ASR.